Peningkatan Pemahaman Ancaman Bencana Siswa SMPN 5 Candipuro Melalui Sosialiasi dan Simulasi - Dina Ruslanjari; Sigit Sulistiyo (Yayasan REDI Tiga Monas, 2024)
Sumbermujur is one of the areas affected by the eruption of Mount Semeru in 2021. One of the impacts was the damage to several facilities, including the buildings of SMPN 5 Candipuro. Therefore, community service needs to be carried out through disaster awareness and simulation activities at the school. The purpose of these activities is to provide an overview of the disaster threats in Sumbermujur and specifically at SMPN 5 Candipuro, and to enhance the understanding and awareness of disaster risks among the school community. The method used in the implementation of the service is the service learning (SL) approach through socialization and participatory action research (PAR) through simulation. The results of the service include the identification of potential disaster threats in Sumbermujur, which has potential threats of extreme weather, earthquakes, forest and land fires, drought, volcanic eruptions, and landslides. SMPN 5 Candipuro, as the location for community service, has 4 potential disaster threats. Efforts to increase the capacity of the school community are carried out through socialization and simulation. The socialization and simulation activities aim to increase the understanding and awareness of the school community about potential disaster threats and to improve preparedness in facing disasters. The evaluation of the activities recommends the creation of evacuation routes as a basic means of evacuation during disasters. The community service activities have provided understanding and increased awareness among the school community of the disaster threats in the surrounding environment.